Benefit of the NeQuick Galileo Version in GNSS Single-Point Positioning. (27th November 2013) - Angrisano, Antonio; Gaglione, Salvatore; Gioia, Ciro; Massaro, Marco; Troisi, Salvatore
Abstract : The GNSS measurements are strongly affected by ionospheric effects, due to the signal propagation through ionosphere; these effects could severely degrade the position; hence, a model to limit or remove the ionospheric error is necessary. The use of several techniques (DGPS, SBAS, and GBAS) reduces the ionospheric effect, but implies the use of expensive devices and/or complex architectures necessary to meet strong requirements in terms of accuracy and reliability for safety critical application. The cheapest and most widespread GNSS devices are single frequency stand-alone receivers able to partially correct this kind of error using suitable models. These algorithms compute the ionospheric delay starting from ionospheric model, which uses parameters broadcast within the navigation messages. NeQuick is a three-dimensional and time-dependent ionospheric model adopted by Galileo, the European GNSS, and developed by International Centre for Theoretical Physics (ICTP) together with Institute for Geophysics, Astrophysics, and Meteorology of the University of Graz. The aim of this paper is the performance assessment in single point positioning of the NeQuick Galileo version provided by ESA and the comparison with respect to the Klobuchar model used for GPS; the analysis is performed in position domain and the errors are examined in terms of RMS and maximum error for the horizontal and vertical components. A deep analysis is also provided for the application of the exanimated model in the first possible Galileo only position fix.